The mathematical experience - Davis, Philip J., 1923-; Hersh, Reuben, 1927- (Boston : Houghton Mifflin, 1982)
Explores the foundations of mathematics, looking at the history and philosophy of the field, and includes biographical sketches of people who have made mathematics their life's work.
Reprint. Originally published: Boston : Birkhäuser, 1981.
Includes bibliographical references and index.
Adult
Keywords: Mathematics -- History; Mathematics -- Philosophy; Mathematics -- Study and teaching; Mathematics -- History; Mathematics -- Philosophy; Mathematics -- Study and teaching